2007
DOI: 10.1257/aer.97.5.1921
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and Heterogeneity of Individual Behavior under Uncertainty

Abstract: By using graphical representations of simple portfolio choice problems, we generate a very rich dataset to study behavior under uncertainty at the level of the individual subject. We test the data for consistency with the maximization hypothesis, and we estimate preferences using a two-parameter utility function based on Faruk Gul (1991). This specification provides a good interpretation of the data at the individual level and can account for the highly heterogeneous behaviors observed in the laboratory. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
405
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(433 citation statements)
references
References 22 publications
23
405
5
Order By: Relevance
“…Choi, Fisman, Gale, and Kariv 2007a, Fisman, Kariv, and Markovits 2007, Andersen, Harrison, Lau, and Rutström 2008, Fisman, Jakiela, and Kariv 2014, we observe tremendous individual heterogeneity in preferences, much of which is not explained by demographic and socioeconomic characteristics. The 5 th percentile ofβi is 0.164, and the 95 th percentile is 1.598.…”
Section: Individual-level Analysismentioning
confidence: 82%
See 3 more Smart Citations
“…Choi, Fisman, Gale, and Kariv 2007a, Fisman, Kariv, and Markovits 2007, Andersen, Harrison, Lau, and Rutström 2008, Fisman, Jakiela, and Kariv 2014, we observe tremendous individual heterogeneity in preferences, much of which is not explained by demographic and socioeconomic characteristics. The 5 th percentile ofβi is 0.164, and the 95 th percentile is 1.598.…”
Section: Individual-level Analysismentioning
confidence: 82%
“…However, the hypothesis that individual preferences are heterogeneous (across individuals) has now been confirmed in a large number of controlled lab experiments (cf. Andreoni and Miller 2002, Choi, Fisman, Gale, and Kariv 2007a, Fisman, Kariv, and Markovits 2007, Andersen, Harrison, Lau, and Rutström 2008, Von Gaudecker, van Soest, and Wengström 2011, Choi, Kariv, Müller, and Silverman 2014, Fisman, Jakiela, and Kariv 2014. Whether future work will also rule out the hypothesis that preferences are stable over time -at least after one properly controls for variation in income, prices, and other arguments that enter into the utility function -remains to be seen; however, we take this assumption as a natural point of departure for economic research, and focus on explanations for variation in revealed preferences (within individual over time) that are related to predictable variation in income and anticipated expenditures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 To quote Echenique, Lee, andShum (2011, p. 1205), " [i]t is fair to say that most of the empirical literature, using both field and experimental data, finds relatively few violations of GARP" 2 Both findings of consistent and heterogenous behavior are confirmed by Choi, Fisman, Gale, and Kariv (2007) in the context of risk-preferences, see also Dean and Martin (2010, Section 5.2…”
Section: Introductionmentioning
confidence: 99%